Orientación al suicidio en adolescentes en una zona de Medellín, Colombia (2014)
ABSTRACT: The risk of suicide orientation is a state preceding suicidal ideation that can lead to a suicide attempt and, possibly, to a successful suicide. Given its magnitude and the pressure it exerts on health systems, suicide is considered a topic of interest for public health. Objective: the study sought to determine the association of suicide orientation risk with: sociodemographic variables and mental health indicators such as: domains of depression, family functioning, family vulnerability and psychoactive substance consumption among adolescent students in the northwest area of Medellin, 2010. Methodology: the researchers performed a cross-sectional study with a random sample of 604 students. The following instruments were used: Inventory of Suicide Orientation (iso 30), Children's Depression Inventory (cdi-la), ¿How is your family? Composite International Diagnostic Interview (cidi ii) and the Apgar family test. Similarly, a confirmatory factor analysis and a logistic regression were conducted. Results: there is association between suicide orientation risk among adolescent students and the following indicators: accumulation of stress in the family, poor search for support, poor family functioning, vulnerability in their moral values and presence of depression symptoms. Conclusion: good family functioning is a very important immediate strategy for achieving good mental health among adolescent students.